you're solving for b -.-
so it should be "b = something"
b = P+c-a
2007-01-17 10:47:49
·
answer #1
·
answered by Taras 2
·
0⤊
0⤋
NO
If you wanna solve for b, you need to get b on one side of the equal sign by itself.
Not only that You divided both sides by b, but b wasn't being multiplied by anything. You use division to undo multiplication.
The way to solve your problem is this. Knowing we want b by itself and seing a +a and -c we can very simply get b by itself.
We undo addition by subtraction and vice versa. So to undo the +a we want to subtract a from both sides as follows:
P (-a) = a + (-a) + b -c The +a and -a on the right cancel
So we now have...
P - a = b - c
We're not done. To undo the -c we have to add. So we'll add +c to both sides as follows:
P - a (+ c) = b - c (+ c) The -c and + c on the right cancel
So we have...
P - a + c = b
That is your answer, notice b is by itself.
Hope this helps, Good Luck with your Math.
2007-01-17 18:46:49
·
answer #2
·
answered by Chaney34 5
·
0⤊
0⤋
No.
P = a + b - c
P + c = a + b - c + c (add c to both sides does not change the equation)
this gives P +c = a + b (the +c - c = 0)
P + c - a = a + b -a (adding a does nothing to the equation)
P + c -a = b (a - a = 0)
2007-01-17 18:49:27
·
answer #3
·
answered by Modus Operandi 6
·
0⤊
0⤋
You are wrong.
Given
P=a+b-c
Subtract a from both sides.
P-a=b-c
Add c to both sides.
P-a+c=b
Solution
b=P-a+c
2007-01-17 18:56:08
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
solving for b is p-a+c =b
2007-01-17 18:48:24
·
answer #5
·
answered by calf_baby 2
·
0⤊
0⤋
no if youare solving for b, you want to get it by itself. P+c-a=b.
2007-01-17 18:48:38
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
No, b= P-a +c
2007-01-17 18:47:58
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋